Estimation of yield of dry air bladders from eel fish - Krishna Rao, K., Basu, S., Panduranga Rao, C.C. and (Fishery Technology, 2021)
The findings are presented of a study conducted to determine a method for the calculation of the yield of dried air bladders of eel from the weight of the whole fish.